Links of the Plasmapause With Other Boundary Layers of the Magnetosphere: Ionospheric Convection, Radiation Belt Boundaries, Auroral Oval - Pierrard, V.; Botek, E.; Ripoll, J.-F.; Thaller, S. A.; Moldwin, M. B.; Ruohoniemi, M.; Reeves, G. (Frontiers in Astronomy and Space Sciences, 2021)
The plasmapause marks the limit of the plasmasphere and is characterized by a sudden change in plasma density. This can influence the other regions of the magnetosphere, including due to different waves circulating inside and outside the plasmasphere. In the present work, we first compare the positions of the plasmapause measured by the NASA Van Allen Probes in 2015 with those of the SWIFF plasmasphere model (SPM). Using the Van Allen Probes and other satellite observations like PROBA-V, we investigate the links that can exist with the radiation belt boundaries. The inward motion of the outer radiation belt associated with sudden flux enhancements of energetic electrons can indeed be directly related to the plasmapause erosion during geomagnetic storms, suggesting possible links. Moreover, the position of the plasmapause projected in the ionosphere is compared with the ionospheric convection boundary. The equatorward motion of the plasmapause projected in the ionosphere is related to the equatorward edge motion of the auroral oval that goes to lower latitudes during storms due to the geomagnetic perturbation, like the low altitude plasmapause and the outer radiation belt. The links between these different regions are investigated during quiet periods, for which the plasmasphere is widely extended, as well as during geomagnetic storms for which plumes are generated, and then afterwards rotates with the plasmasphere. The magnetic local time dependence of these boundaries is especially studied on 14 March 2014 after a sudden northward turning of the interplanetary magnetic field (IMF) and for the geomagnetic storm of 26 August 2018, showing the importance of the magnetic field topology and of the convection electric field in the interactions between these different regions eventually leading to the coupling between magnetosphere and ionosphere.